Faktor-faktor Yang Mempengaruhi Corporate Social Responsibility Disclosure (CSRD) - Sulis Rochayatun (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2016)
Along with the modern civilization the existence of a company or the business world continues to be in the spotlight. One important issue that continues to be the attention of the business world today is a matter of corporate social responsibility (Corporate Social Responsibility), hereinafter abbreviated CSR in this writing. As part of the configuration of the relationship between business and society, the issue of corporate social responsibility undergo a conceptual formulation that is constantly changing, in line with the growth experienced by the business itself. The concept of triple bottom lines declared that corporations are not only responsible for its financial condition (financial) alone, as in the single bot tom line, but also pay attention to social and environmental problems. Therefore it is important to know what factors influence the disclosure of corporate social responsibility. This study aims to determine the effect of variable environmental performance that the environmental performance of companies are assessed based PROPER, environmental performance superior to encourage companies to increase CSR, and variable corporate governance mechanism proxy for institutional ownership, board of directors, independent board and audit committee, with the Good Corporate Governance will encourage companies do CSR. corporate social responsibility disclosure (CSRD) use indicators of the Global Reporting Intiative (GRI) .The design research is associative causality. The population of 137 companies listed in Indonesia Stock Exchange period 2011-2013, with the purpose of sampling the company acquired as many as 15 samples. Multiple regression analysis used in this study. The results showed that the environmental audit committee performance and significant positive effect on CSRD. While the corporate governance mechanism proxy for ownership institusionaldan independent board does not affect the CSRD. This shows that the higher the ranking of environmental performance, it will be followed by an increase CSRD and the better the mechanisms of supervision on the management, good corporate governance will be created that will encourage to do CSRD.